Two Desdemona or Modern Reconsideration of the Image of Desdemona. (Eurasian Journal of Philology Science and Education, 2015)
The play of T. Morrison «Desdemona» created on the basis of the tragedy of W. Shakespeare «Othello» represents a new view on the theme developed by the classic. T. Morrison’s Desdemona in accordance with the African traditions comes back from the world of spirits to the living world as though she administers a secret court. The whole work is based on contrasts that allow the author to raise more convex problems which did not sound at full in the play of Shakespeare. Desdemona loves Othello as he is, and Othellounderstands that he isn’t worthy of her. Returning to the living Desdemona lifts the veil over many secrets, but she does not administer the final court. The final of the play remains open.
Keywords: Shakespeare; Morrison; «Othello»; Desdemona; play